Moose browsing in a Scots pine plantation mixed with deciduous tree species. - Heikkilä, Risto (The Society of Forestry in Finland - The Finnish Forest Research Institute, 2009)
Studies were made at Lapinjarvi, S. Finland, in May and September 1987 and May 1988 on the utilization of available food resources by moose (Alces alces) in a Scots pine (Pinus sylvestris) plantation containing an admixture of deciduous species. Rowan (Sorbus aucuparia) and aspen (Populus tremula) were preferred-food compared to pine and both silver birch (Betula pendula) and pubescent birch (B. pubescens). However, rowan and aspen were not capable of withstanding continuous browsing by moose owing to their diminished biomass. The browsing intensity (number of browsed twigs/tree) on pine and birch was about twice that on rowan and aspen. The number of browsed twigs per tree increased as the amount of available main branches increased. The number of bites per available branch, as well as the maximum diameter of the bites, decreased as the density of the plantation increased. Silver birch was preferred to pubescent birch; planted silver birch was preferred to naturally regenerated trees. Main stem breakage was especially common in winter 1988; the average height of pine and birch was >2 m. The tops of broken stems were commonly utilized as food. The increase in moose density and the relatively deep snow cover promoted the incidence of serious damage. The number of undamaged trees/ha was greater in dense than in sparse parts of the stand.